2012
DOI: 10.1177/1354068811436049
|View full text |Cite
|
Sign up to set email alerts
|

Political parties and rallies in Latin America

Abstract: This article provides a novel answer to explain the persistence of party rallies in the mass and social media era. I argue that rallies contribute to the organizational structure of clientelistic parties by providing information to different members within and outside the machine. Rallies provide party leaders with information that enables them to monitor brokers’ capacity to mobilize voters, party brokers with an opportunity to display their ability to turn out voters while monitoring voters’ responses, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…La perduración de los mítines políticos en la era de las comunicaciones sociales masivas se explica porque contribuyen a cimentar la estructura organizativa de los partidos clientelistas, ya que brindan información sobre la participación -y las oportunidades para ello-de distintos miembros, dentro y fuera del aparato partidario (Szwarcberg 2014). A los dirigentes, los mítines les dan información que les permite controlar la capacidad de los candidatos para movilizar votantes.…”
Section: Marco Empíricounclassified
“…La perduración de los mítines políticos en la era de las comunicaciones sociales masivas se explica porque contribuyen a cimentar la estructura organizativa de los partidos clientelistas, ya que brindan información sobre la participación -y las oportunidades para ello-de distintos miembros, dentro y fuera del aparato partidario (Szwarcberg 2014). A los dirigentes, los mítines les dan información que les permite controlar la capacidad de los candidatos para movilizar votantes.…”
Section: Marco Empíricounclassified
“…Parties have to rely on intermediaries to target and transfer particularistic inducements to voters (Koter, 2013;Szwarcberg, 2012). Kitschelt and Kselman (2011) have found that civic associations can serve as intermediaries, because they can coordinate members and establish group consensus, and their "special interest" character is likely to make them more amenable to engage with clientelistic political parties.…”
Section: The Effect Of Party Organization and Economic Institutionsmentioning
confidence: 99%
“…Using rich administrative data, we provide quantitative evidence that these monitoring efforts are systematic and are consistent with the theoretical argument. We first empirically assess whether brokers effectively mobilize voters en masse to make their mobilization efforts more visible to the decentralized party machine (Stokes et al 2013;Szwarcberg 2014). Second, we analyze whether the incumbent party-but not the main opposition partyexperiences greater electoral support when its machine's monitoring capacity is greater (Larreguy 2013;Larreguy, Marshall, and Querubin 2016).…”
mentioning
confidence: 99%
“…In what constitutes a classical agency problem, parties must construct noisy signals about brokers' performance and set up signal‐contingent incentives to maximize their voter mobilization efforts and, consequently, their electoral prospects (Larreguy 2013; Stokes et al. 2013; Szwarcberg 2014). Improved monitoring capacity increases broker effort, which improves electoral results.…”
mentioning
confidence: 99%